Implementasi Program ISMUBA (Al-Islam Kemuhammadiyahan dan Bahasa Arab) Melalui Kegiatan Muhadhoroh dalam Membentuk Sikap Percaya Diri Siswa di SMA Muhammadiyah 8 Ciputat - Mahliga Fitriansyah; Siti Shofiyah; Ummah Karimah; Vina Inayatul Matin (IQRO: Journal of Islamic Education, 2024)
The emergence of the 4.0 age has increasingly caused the younger generation to rely on technology in every part of their lives. This is detrimental to society, especially for those who would rather use social media than interact with others in class. While they surf in the virtual world, they are less secure in the real world. This study aims to clarify how the religious program, muhadhoroh, is implemented to form the students' self-confidence at SMA Muhammadiyah 8 Ciputat, South Tangerang. This study employs a descriptive qualitative research methodology. Utilizing interviews and observation as data collection methods. Data reduction was used to analyze this study's data. According to the survey, muhadhoroh exercises help pupils become more confident while enhancing their language and communication skills, resulting in positive outcomes. The muhadhoroh activities are conducted regularly every Friday, and the officers are scheduled to take turns from each class.